Towards the liberation of labour markets in Europe - Oliveira, L. (2017)
One of the objectives of this article is to understand to what extent precarious employment is disseminated in European Union (EU) countries and to analyse if it is a conjuncture phenomenon or if it represents a structural reconfiguration of the labour markets. This analysis was carried out by comparing three generationsin different periods of time. We used statistical information about precarious employment and comparisons within and between EU countries (Eurostat 1985;1995; 2005) over the past 20 years, using a multidimensional method: principal components analysis for categorical data. We concluded that the labour markets in Europe are showing a structural change in the direction of defining a new salary relation, which we have termed ‘neo-competitive’. All the countries are movingtowards a greater liberalisation of the employment relationship, through easier dismissal processes, or by the expansion of precarious employment or a combination of both.